Eradication of measles: remaining challenges - Holzmann, Heidemarie; Hengel, Hartmut; Tenbusch, Matthias; Doerr, H. W. (Medical Microbiology and Immunology, 2016)
Measles virus (MeV) is an aerosol-borne and one of the most contagious pathogenic viruses known. Almost every MeV infection becomes clinically manifest and can lead to serious and even fatal complications, especially under conditions of malnutrition in developing countries, where still 115,000 to 160,000 patients die from measles every year. There is no specific antiviral treatment. In addition, MeV infections cause long-lasting memory B and T cell impairment, predisposing people susceptible to opportunistic infections for years. A rare, but fatal long-term consequence of measles is subacute sclerosing panencephalitis. Fifteen years ago (2001), WHO has launched a programme to eliminate measles by a worldwide vaccination strategy. This is promising, because MeV is a human-specific morbillivirus (i.e. without relevant animal reservoir), safe and potent vaccine viruses are sufficiently produced since decades for common application, and millions of vaccine doses have been used globally without any indications of safety and efficacy issues. Though the prevalence of wild-type MeV infection has decreased by >90 % in Europe, measles is still not eliminated and has even re-emerged with recurrent outbreaks in developed countries, in which effective vaccination programmes had been installed for decades. Here, we discuss the crucial factors for a worldwide elimination of MeV: (1) efficacy of current vaccines, (2) the extremely high contagiosity of MeV demanding a >95 % vaccination rate based on two doses to avoid primary vaccine failure as well as the installation of catch-up vaccination programmes to fill immunity gaps and to achieve herd immunity, (3) the implications of sporadic cases of secondary vaccine failure, (4) organisation, acceptance and drawbacks of modern vaccination campaigns, (5) waning public attention to measles, but increasing concerns from vaccine-associated adverse reactions in societies with high socio-economic standards and (6) clinical, epidemiological and virological surveillance by the use of modern laboratory diagnostics and reporting systems. By consequent implementation of carefully designed epidemiologic and prophylactic measures, it should be possible to eradicate MeV globally out of mankind, as the closely related morbillivirus of rinderpest could be successfully eliminated out of the cattle on a global scale.
EVALuna2:8323